How to solve this PreCalc problem?

Verify showing all steps in the process.

tanx

-------- = cscx (1+ secx)

1-cosx

1 Answer

Relevance
  • 6 years ago
    Favorite Answer

    Given:

    tanx

    -------- = cscx (1+ secx)

    1-cosx

    Consider LHS:

    tanx/(1-cosx)=sinx / ((cosx) (1-cosx))

    Divide and multiply with 1+cosx in numerator and denominator

    = sinx (1+cosx)/((cosx) (1-cosx) (1+cosx))

    = sinx(1+cosx)/ ((cosx) (1-cos^2 x))

    = sinx(1+cosx)/((cosx) (sin^2 x))

    = (1+cosx)/((cosx) (sin x))

    = (1+cosx)/cosx * cscx

    = (secx+1) *cscx

    = cscx(1+secx)

    =Right hand side term

    Hence proved

Still have questions? Get your answers by asking now.